(untitled) (Research, Society and Development, 2021)
Introduction: Pertussis is an acute infectious disease of high transmissibility and an important cause of childhood morbidity and mortality. It is caused by the bacteria Bordetella pertussis and B. parapertussis, and man is its only natural reservoir, affecting the respiratory system, especially the trachea and bronchi. It is mainly transmitted by the direct contact of the sick person with a susceptible, unvaccinated person, through droplets of saliva expelled by coughing, sneezing or saliva, as well as by contact with objects contaminated with the patient’s secretions. Objective: to attest, through public data of notifications of cases of incidence of this disease, the drop in these numbers in Brazil. in 2020, compared to the previous year. Methodology: This is a descriptive and quantitative epidemiological study. The search for pertussis cases in the years 2019 and 2020, registered in the Information System for Notifiable Diseases (SINAN) - DATASUS, was carried out. Results and discussion: the closing of schools and day care centers led to an immediate and dramatic reduction in contacts between children and, consequently, in communicable infections, which are the cause of most pediatric health consultations Conclusion: the dramatic reduction in infectious diseases Communicable diseases leads to an opportunity to study the incidence of diagnoses that are presumed but not definitively proven to be caused by infections. Although the circumstantial evidence base for this effect is broad, the current analysis adds even more to this, as the relative reduction in presumed diagnoses of infection can be as large as the reduction in communicable infections.